APPROACHING ETHNO-RELIGIOUS IDENTITY - Хачатурян, Нелли Рафиковна (History, Archeology and Ethnography of the Caucasus, 2024)
The development of modern societies is largely associated with ethno-religious and religious processes. The study of ethnicities, societies or other groups through the prism of religious processes, first of all, aims to identify the impact of religious consciousness and behavior on the processes of reproduction of ethnic or group identity. It is the religion that is most often associated with ethnic or group culture. Due to the characteristics of the country of residence, religious, ethnic, cultural or political segments, the same ethnic or other group may exhibit differing religious behaviors. Religious processes have become a prominent topic of social inquiry, with scholars across various disciplines examining concepts like religiosity, religious identity, worldview, consciousness, and behavior. This area of study presents a crucial, intriguing, and inherently complex facet of modern social sciences. Yet, the question of theoretical and methodological approaches in studying this subject remains open in scientific discourse. For example, the issues of religiosity often go beyond the scope of theoretical research, and their social significance requires the use of applied analytical capabilities, as the latter is dictated by the need to identify the place of religious consciousness and behavior in social processes in the context of transformation of modern societies and during periods of reforms and crisis. Religious belonging, practices and traditions are the key factors in defining cultural identity of an ethnic/religious minority groups. The emphasis becomes stronger in multi-religious societies, where religion and religious affiliation determine the self-identity of a group, thus becoming one of the pillars of preserving its cultural heritage. This paper examines the unique challenges and considerations involved in studying the phenomenon of ethno-religious identity. It analyzes the complex interplay between ethnic and religious identities that forms the core structure of ethno-religious identity. Drawing on the author’s research experience, the paper provides an overview of the theoretical, ideological, and empirical approaches utilized in studying this complex phenomenon.